408 THE PRESENCE OF LYMPHATIC, VENOUS AND PERINEURAL INFILTRATION FOLLOWING ESOPHAGECTOMY WITHOUT NEOADJUVANT THERAPY TO IDENTIFY PATIENTS AT RISK OF RECURRENCE. (14th September 2020) - Hardy, K; Chmelo, J; Khaw, R; Navidi, M; Phillips, A
Abstract: : Staging and prognostication in esophgaeal cancer patients is based on their TNM stage. Previous research has suggested venous invasion (VI), lymph vessel invasion (LI) and perineural invasion (PNI) as adverse prognostic indicators in patients with advanced disease receiving neoadjuvant treatment. The aim of this study was to assess the incidence and prognostic significance of these factors in patients with cancer of the esophagus or gastro-esophageal junction (GEJ) who were treated with unimodality surgery. Methods: A contemporaneously maintained database was used to identify patients who underwent a primary 2-field transthoracic esophagectomy for adenocarcinoma or squamous cell carcinoma of the esophagus or gastro-esophageal junction. Between January 2000 and January 2018. Patients who died in hospital, underwent palliative resections or where the presence (or absence) of VI, LI or PNI was not reported were excluded. Patients were staged using UICC-TNM 7. Results: 279 patients were included. VI was present in 99 (35%) patients, LI in 120 (43%), and PNI in 120 (43%). Median overall survival was 140 months (95% confidence interval (CI): 79.3–200.7) when PNI, LV and VI were absent, 55 months (95% CI: 42.2–67.8) when one factor was present, 18 months (95% CI: 5.4–30.6) with two factors and 31 months (95% CI: 17.6–44.4) with all three factors present. Univariable analysis revealed that LI, PNI and VI are significant prognostic indicators for length of disease-free survival (p < 0.001) with LI an independent prognostic factor on multivariable analysis (p = 0.05). Conclusion: These findings suggest the importance of the presence of LI, VI and PNI in patients undergoing unimodality esophagectomy for cancer of the esophagus. It may provide additional information for identifying patients that are high risk who may be candidates for adjuvant therapy.